2015
DOI: 10.1002/dvg.22910
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a KORCre knockin mouse strain to study cells involved in kappa opioid signaling

Abstract: The kappa opioid receptor (KOR) has numerous important roles in the nervous system including the modulation of mood, reward, pain, and itch. In addition, KOR is expressed in many non-neuronal tissues. However, the specific cell types that express KOR are poorly characterized. Here, we report the development of a KOR-Cre knockin allele, which provides genetic access to cells that express KOR. In this mouse, Cre recombinase (Cre) replaces the initial coding sequence of the Opkr1 gene (encoding the kappa opioid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…A subpopulation of primary afferents in the mouse is known to respond to KOR agonists (Macdonald and Werz, 1986; Werz and Macdonald, 1984), but this subpopulation has not been characterized. We therefore generated a KOR-cre knockin allele in which Cre recombinase (Cre) replaces the initial coding sequence of the Oprk1 gene (Cai et al, 2016). To validate that the KOR-cre allele mediates recombination in primary afferents that express Oprk1, we performed dual fluorescent in-situ hybridization (FISH) for Oprk1 and tdTomato mRNA in mice that had received intrathecal administration of a Cre-dependent virus (AAV.FLEX.ChR2-tdTomato) (Dayton et al, 2012; Vulchanova et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subpopulation of primary afferents in the mouse is known to respond to KOR agonists (Macdonald and Werz, 1986; Werz and Macdonald, 1984), but this subpopulation has not been characterized. We therefore generated a KOR-cre knockin allele in which Cre recombinase (Cre) replaces the initial coding sequence of the Oprk1 gene (Cai et al, 2016). To validate that the KOR-cre allele mediates recombination in primary afferents that express Oprk1, we performed dual fluorescent in-situ hybridization (FISH) for Oprk1 and tdTomato mRNA in mice that had received intrathecal administration of a Cre-dependent virus (AAV.FLEX.ChR2-tdTomato) (Dayton et al, 2012; Vulchanova et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…KOR-cre mice were generated as previously described and are maintained on a mixed C57bl/6.129J background (Cai et al, 2016). For some electrophysiological and anatomical experiments, KOR-cre mice were mated with Ai9 (Cre-responsive tdTomato reporter) mice or with Ai32 (Cre-responsive ChR2-eYFP) mice (The Jackson Laboratory).…”
Section: Star Methodsmentioning
confidence: 99%
“…KOPR expression and function in DRG can now also be investigated with reporter mice (Cai et al 2016, Liu-Chen 2017). Multiple preclinical studies provided evidence that KOPR in DRG may control visceral pain and suggested the use of peripherally restricted kappa agonists for these types of pain (Kivell & Prisinzano 2010, Vanderah 2010).…”
Section: Neuroanatomical Substrates For Opioid Analgesiamentioning
confidence: 99%
“…For instance, the identification of MOPR-expressing neuronal populations in affective circuits that mediate opioid-induced reductions in pain affect will enable transcriptional and proteomic studies to uncover novel nonopioid analgesic targets. These studies are facilitated by the development of genetically engineered mouse lines for visualizing and manipulating opioid receptor-expressing neurons (Cai et al 2016, Erbs et al 2015, Scherrer et al 2006). Similar tools can now be used in vivo to study the cells that endogenously release enkephalins, dynorphins, endorphins, and nociceptin (Al-Hasani et al 2015, Cowley et al 2001, Francois et al 2017).…”
Section: Conclusion: Dissociating Deleterious Side Effects From Analmentioning
confidence: 99%
“…2). RGS12 may also regulate KOR-mediated spinal-analgesia via similar mechanisms: RGS12 and KOR are both expressed in spinal-neurons that mediate analgesia [38,96,97]. Dorsal-rootganglion (DRG) neurons located adjacent to the spinal-cord, as well as the dorsal-horns, represent key nociceptive loci as they contain neurons responsible for receiving and transmitting nociceptive-signals [98].…”
Section: Discussionmentioning
confidence: 99%